The Assistance Economic Independence through Making Fermented Animal Feed in the Cattle Farmer Community at Rejomulyo Sub-District South Metro - Andika Ari Saputra; Haris Santoso; M. Zainal Arifin (International Journal of Community Engagement Payungi, 2021)
The condition of a developing country associates with other nations that have advanced economically. In an effort to catch up in the economic field, these countries must carry out various development programs. Farmers and underprivileged communities in the regions need assistance or funds that aim to empower them. The aim of this article gave the Assistance for Economic Independence through Making Fermented Animal Feed in the Cattle Farmer Community at Rejomulyo Sub-District South Metro, The researchers used Asset Based Community Development (ABCD), by conducting training to the farmers about the importance of utilizing the potential that exists in the environment. The result show that the community empowerment provides benefits in the form of increasing knowledge of the nutrients needed by livestock, high nutritional animal feed, increasing skills in making fermented hay feed through training activities both theory and practice. For the success of the service carried out, there was still need for further assistance to cattle breeders.